Little Bob - Rohman, Cricket (Zaner-Bloser, Inc.)
Little Bob, What's on the dock? A rock, a clock, and a sock.What's in the shop? A mop, a top, and a pork chop. What's in the box? A fox, an ox, and$1! = (Bchicken pox!s
Keywords: Rhymes